Berberine Improves Glucose and Lipid Metabolism in HepG2 Cells Through AMPKα1 Activation - Ren, Gang; Guo, Jiang-Hong; Qian, Yu-Zhen; Kong, Wei-Jia; Jiang, Jian-Dong (Frontiers in Pharmacology, 2020)
Aim: This study is designed to investigate whether or not AMP-activated protein kinase α1 (AMPKα1) is required for natural product berberine (BBR) to improve glucose and lipid metabolism in HepG2 cells. Methods: AMPKα1 knocked-out (KO, AMPKα1-/-) cells were obtained by co-transfection of the CRISPR/Cas9 KO and HDR (homology-directed repair) plasmid into HepG2 cells, as well as subsequent screen with puromycin. The expression levels of target proteins or mRNAs were determined by western blot or real-time RT-PCR, respectively. Cellular AMPK activity, glucose consumption, lactate release, glucose production, and lipid accumulation were determined by kits. Results: The results showed that the AMPKα1 gene was successfully KO in HepG2 cells. In AMPKα1-/- cells, the protein expression of AMPKα1 and phosphorylated-AMPKα1 (p-AMPKα1) disappeared, the level of total AMPKα declined to about 45%-50% of wild type (p<0.01), while p-AMPKα level and AMPK activity were reduced to less than 10% of wild type (p<0.001). BBR increased p-AMPKα1, p-AMPKα, AMPK activity, and stimulated glucose consumption, lactate release, inhibited glucose production in wild type HepG2 cells (p<0.05 or p<0.01). BBR also reduced intracellular lipid accumulation and suppressed the expression of lipogenic genes in oleic acid (OA) treated wild type HepG2 cells (p<0.05 or p<0.01). In AMPKα1-/- HepG2 cells, the stimulating effects of BBR on p-AMPKα1, p-AMPKα, AMPK activity, and its improving effects on glucose and lipid metabolism were completely abolished. Conclusion: Our study proves that AMPKα1 plays a critical role for BBR to improve glucose and lipid metabolism in HepG2 cells. Our results will provide new information to further understand the molecular mechanisms of BBR.